THE CHALLENGES IN DEVELOPING SPEAKING SKILL AND WAYS TO OVERCOME - Qodirova , Shohsanam Alisher qizi (Innovative Development in Educational Activities, 2024)
This article contains general information about the difficulties in speaking competence in simultaneous interpretation. There are given alternative exercises to enhance this skill.